Cluster randomised feasibility trial to improve the Control of Hypertension In Rural India (CHIRI): a study protocol. Issue 10 (8th October 2016) - Riddell, Michaela A; Joshi, Rohina; Oldenburg, Brian; Chow, Clara; Thankappan, K R; Mahal, Ajay; Thomas, Nihal; Srikanth, Velandai K; Evans, Roger G; Kalyanram, Kartik; Kartik, Kamakshi; Maulik, Pallab K; et al.
Abstract : Introduction: Hypertension is emerging in rural populations of India. Barriers to diagnosis and treatment of hypertension may differ regionally according to economic development. Our main objectives are to estimate the prevalence, awareness, treatment and control of hypertension in 3 diverse regions of rural India; identify barriers to diagnosis and treatment in each setting and evaluate the feasibility of a community-based intervention to improve control of hypertension. Methods and analysis: This study includes 4 main activities: (1) assessment of risk factors, quality of life, socioeconomic position and barriers to changes in lifestyle behaviours in ∼14 500 participants; (2) focus group discussions with individuals with hypertension and indepth interviews with healthcare providers, to identify barriers to control of hypertension; (3) use of a medicines-availability survey to determine the availability, affordability and accessibility of medicines and (4) trial of an intervention provided by Accredited Social Health Activists (ASHAs), comprising group-based education and support for individuals with hypertension to self-manage blood pressure. Wards/villages/hamlets of a larger Mandal are identified as the primary sampling unit (PSU). PSUs are then randomly selected for inclusion in the cross-sectional survey, with further randomisation to intervention or control. Changes in knowledge of hypertension and risk factors, and clinical and anthropometric measures, are assessed. Evaluation of the intervention by participants provides insight into perceptions of education and support of self-management delivered by the ASHAs. Ethics and dissemination: Approval for the overall study was obtained from the Health Ministry's Screening Committee, Ministry of Health and Family Welfare (India), institutional review boards at each site and Monash University. In addition to publication in peer-reviewed articles, results will be shared with federal, state and local government health officers, local healthcare providers and communities. Trial registration number: CTRI/2016/02/006678 ; Pre-results.